Effect of 4 Weeks of High-Intensity Interval Training (HIIT) on VO2max, Anaerobic Power, and Specific Performance in Cyclists with Cerebral Palsy - Cristian A. Lasso-Quilindo; Luz M. Chalapud-Narvaez; Diego C. Garcia-Chaves; Carlos Cristi-Montero; Rodrigo Yañez-Sepulveda (Journal of Functional Morphology and Kinesiology)
Background: High-intensity interval training (HIIT) is an effective and efficient method for training Paralympic athletes with cerebral palsy, particularly in intermittent sports and those requiring aerobic and anaerobic capacity, speed, and strength to delay fatigue onset and optimize athletic performance. Objectives: This study aimed to analyze the effects of four weeks of HIIT on the estimated VO2max, anaerobic power, and athletic performance in cyclists with cerebral palsy. Materials and Methods: This quasi-experimental study included three male athletes (Athletes A, B, and C) with cerebral palsy from the Paracycling Departmental Commission of Cauca, Colombia. The estimated VO2max was assessed using an incremental test on a cycling ergometer. Anaerobic power was measured using the 30 s long Wingate Anaerobic Test (WAnT_30 s. Specific performance was evaluated with an individual time trial of 14 km for class T1 and 20 km for class T2. HIIT training was performed on a cycling ergometer over four weeks (two sessions per week). The training intensity was based on watts (W) measured in the incremental test for long HIIT sessions and in the WAnT_30 s test for short HIIT sessions. The training load was monitored through heart rate (HR) responses and the subjective perceived exertion (RPE) at the end of the training. Results: After the HIIT intervention, percentage changes in the estimated VO2max were observed in Athlete A (+7%) and Athlete C (+9.4%). In the WAnT_30 s, there were increases in the maximal and mean power in Athlete A (>31%, 282.3 vs. 370.4 W), Athlete B (>15%, 272.5 vs. 312.6 W), and Athlete C (>9%, 473.7 vs. 516.2 W). Individual time trial performance improved, with reduced completion times for Athlete A (−6.7%, 2492 vs. 2325 s), Athlete B (−3.7%, 2486 vs. 2390 s), and Athlete C (−3.7%, 2775 vs. 2674 s). Conclusions: This study found that eight sessions of high-intensity interval training (HIIT) over a four-week period had a positive effect on the estimated VO2max in Athletes A and C. Moreover, all three paracyclists demonstrated improvements in their maximal and average power output during the 30 s Wingate Anaerobic Test (WAnT_30 s), as well as enhanced performance in the time trial test.